Implementasi Kebijakan Penanganan Sampah Laut di Wilayah Pesisir di Kecamatan Ponelo Kepulauan Kabupaten Gorontalo Utara - Ikbal Opi; Asna Aneta; Udin Hamim (Research Review: Jurnal Ilmiah Multidisiplin, 2025)
This study aimed to analyze the implementation of marine debris management policy in the coastal arcas of Ponelo Kepulauan Subdistrict, North Gorontalo Regency. The main problems encountered included the lack of waste disposal sites and the community's habit of littering, which negatively impacted the marine environment and public health. This present study employed a qualitative approach with George C. Edward III's policy implementation theory, which emphasized communication, resources, disposition, and bureaucratic structure. The findings indicated that government communication through outreach to the community has been running well. However, resource availability remains limited, particularly supporting facilities and infrastructure such as cleaning equipment and trash bins. In terms of disposition, local governments, sub-districts, villages, and the community have demonstrated a positive attitude and support for policy implementation. Then, the bureaucratic structure was also deemed adequate, with standard operating procedures (SOPs) and coordination between relevant parties in place, despite the fact that oversight still needs to be improved. This study recommends improving supporting facilities, adding more cleaning staff, and strengthening the government's role in monitoring and enforcing regulations to ensure more effective marine debris management.